KEPUASAN KERJA MEMEDIASI PRODUKTIVITAS DOSEN DAN TENAGA KEPENDIDIKAN SAAT WORK FROM HOME (?) - Afni Sirait; Sri Luna Murdianingrum (Universitas Methodist Indonesia, 2020)
The COVID-19 pandemic has brought many changes in various sectors. The education sector is one of the sectors that is significantly affected and must adapt as soon as possible to changes due to government regulations and policies. The purpose of this research is to analyze the productivity of lecturers and education personnel due to WFH policies and to mediate job satisfaction factors. The population of this study was lecturers and education staff in the FEB UPN